2020
DOI: 10.1002/ijc.33127
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in fibroblasts induced by cigarette smoke extract promotes invasion in lung cancer cells

Abstract: We investigated the effects of cigarette smoke extract (CSE) on lung fibroblasts and found that the invasiveness of lung cancer cells was facilitated by the conditioned medium from CSE‐treated fibroblasts. CSE induced autophagy in fibroblasts and increased the expression of autophagy‐related proteins, including optineurin and Ras‐related protein Rab1B. Afterward, the fibroblasts produced high levels of interleukin‐8 (IL‐8), which promoted cancer cell invasion. The inhibition of either optineurin or Rab1B abrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…Hence, we applied another autophagy inhibitor, autophinib, and got a similar result as CQ treatment. Therefore, studies on autophagy disorders caused by tobacco metabolites can be confirmed, and this phenomenon also exists in other tumors [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we applied another autophagy inhibitor, autophinib, and got a similar result as CQ treatment. Therefore, studies on autophagy disorders caused by tobacco metabolites can be confirmed, and this phenomenon also exists in other tumors [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition optineurin reversed the pathway and reduced p62 protein and IL-8 expression in these treated fibroblasts. Thus, it seems that the IL‐8 expression of cigarette smoke triggered autophagy can support the spread of cancerous lung cells [ 128 ].…”
Section: Therapeutic Implications Of Autophagy Dysregulationmentioning
confidence: 99%
“…Besides, cancer cells can promote autophagy in fibroblasts and induce the release of inflammatory cytokines such as IL6 and IL8 which in turn promote the growth of tumor [ 36 ]. Among previous studies, we have observed tobacco induced autophagy in different kinds of fibroblasts like CAFs of breast cancer [ 37 ] and human lung fibroblasts [ 38 ]. Hou et al verified that exposed to cigarette smoke extract can up-regulate the expression of autophagy-related protein (LB3 and p62) in fibroblasts and promote the secretion of IL8 [ 38 ].…”
Section: The Effect Of Tobacco Product On Fibroblastsmentioning
confidence: 99%
“…Among previous studies, we have observed tobacco induced autophagy in different kinds of fibroblasts like CAFs of breast cancer [ 37 ] and human lung fibroblasts [ 38 ]. Hou et al verified that exposed to cigarette smoke extract can up-regulate the expression of autophagy-related protein (LB3 and p62) in fibroblasts and promote the secretion of IL8 [ 38 ]. It seems that autophagy in stromal fibroblasts caused by external stimuli could also affect the development of cancer cells.…”
Section: The Effect Of Tobacco Product On Fibroblastsmentioning
confidence: 99%